2012
DOI: 10.1007/s10712-012-9205-z
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Charged Particles Above Thunderclouds

Abstract: International audienceThe French government has committed to launch the satellite TARANIS to study transient coupling processes between the Earth's atmosphere and near-Earth space. The prime objective of TARANIS is to detect energetic charged particles and hard radiation emanating from thunderclouds. The British Nobel prize winner C.T.R. Wilson predicted lightning discharges from the top of thunderclouds into space almost a century ago. However, new experiments have only recently confirmed energetic discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 184 publications
1
18
0
Order By: Relevance
“…The agreement between the quasi-static electric field and the high-level discharge activity is excellent (Figure 4, top left and center left panels). A similar example of a high-level discharge activity superimposed on a quasi-static electric field (Figure 4, top right and center right panels) was observed in association with an extremely well-documented example of two consecutive lightning discharges [Füllekrug et al, 2013b]. The source locations of the pulses occurring during the second lightning discharge have been mapped with an array of radio receivers [Mezentsev and Füllekrug, 2013] which shows that their origin are intracloud lightning discharges at an average height of 3.5 km (Figure 4, bottom).…”
Section: Observationssupporting
confidence: 64%
See 1 more Smart Citation
“…The agreement between the quasi-static electric field and the high-level discharge activity is excellent (Figure 4, top left and center left panels). A similar example of a high-level discharge activity superimposed on a quasi-static electric field (Figure 4, top right and center right panels) was observed in association with an extremely well-documented example of two consecutive lightning discharges [Füllekrug et al, 2013b]. The source locations of the pulses occurring during the second lightning discharge have been mapped with an array of radio receivers [Mezentsev and Füllekrug, 2013] which shows that their origin are intracloud lightning discharges at an average height of 3.5 km (Figure 4, bottom).…”
Section: Observationssupporting
confidence: 64%
“…One possible mechanism could be for example electron pileup during which the positive cloud‐to‐ground discharge dislocates electrons with the heavier ions following later to neutralize the electric field produced by the dislocated electrons. Such kind of mechanism could be in operation, for example, if hydrometeors [ Gurevich et al , ; Gurevich and Karashtin , ] or aerosols [ Füllekrug et al , , ] contribute significantly to the observed quasi‐static electric field.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this contribution aims to determine the wave number vectors by use of an array of radio receivers. Specifically, the array analyses developed for seismic and infrasound arrays [e.g., Füllekrug et al, 2013c;Rost and Thomas, 2002;Gaffet et al, 1998;Cansi, 1995] are adapted and subsequently exemplarily applied to ∼20-24 kHz radio waves from radio transmitters for submarine communication to validate the array analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Infrasound is an innovative technique for monitoring continuously the infrasound signals produced by lightning and TLEs in tropical regions where there are no groundbased current observations. They will be very useful for the validation of observation from space of future space mission as TARANIS (Blanc et al 2007;Lefeuvre et al 2008), ASIM (Neubert et al 2009) and associated studies (Füllekrug et al 2013). ARISE will provide a unique database and will contribute to their monitoring in the longer term.…”
Section: Transient Luminous Eventsmentioning
confidence: 99%